BIOSOCIODEMOGRAPHIC AND DIGITAL PROFILE OF PARTICIPANTS IN AN ONLINE EDUCATIONAL INTERVENTION ON COLOSTOMY (Estima – Brazilian Journal of Enterostomal Therapy, 2023)
Objective: To identify the biosociodemographic and digital profile of people with colostomy and caregivers who participated in the online educational intervention on colostomy. Method: Cross-sectional study carried out with 20 people with colostomy and 32 caregivers, in the period of September/November 2020, in an integrated health center in Teresina, Piauí, Brazil. Sociodemographic and clinical characterization instruments, computer and internet access, and basic digital proficiency submitted to statistical analysis were used. Results: Among people with colostomy and caregivers, 60% were male and 75% female. Temporary colostomy (55%) with bright red color and regular shape (80%) predominated. Most caregivers had a job (46.9%), and 8 hours/week were dedicated to care. The degree of digital proficiency was low (76.9%). Conclusion: The identification ofthe biosociodemographic and digital profile of the participants can contribute to the adoption of educational strategies according to digital maturity or the need for support for the use of technologies, to optimize health care and qualify the assistance provided.